RANCANG BANGUN WEB MONITORING SISTEM PADA MESIN KONVERSI LIMBAH ORGANIK MENJADI ENERGI LISTRIK - Puspitawati, Luh Eka; Sukadarmika, Gede; Arsa Suyadnya, I Made (Jurnal SPEKTRUM; Vol 10 No 4 (2023): Jurnal SPEKTRUM, 2023)
UD. Nadi Utama is one of the producers and distributors of traditional snacks. As a snack producer, UD Nadi Utama supplies 5 minimarkets every day. To support its business, UD Nadi Utama installs PLN electricity with an average electricity payment of IDR 750,000 per month which is considered to burden production costs. After conducting observations, the capstone project team found that UD, Nadi Utama produces 25 kg of coconut fiber and shell per day. From the problems and potential found at UD Nadi Utama, team capstone project provides a solution in the form of an incinerator. This incinerator has a converter device that can convert the heat generated from combustion into electrical energy. However, monitoring the data of voltage, current, temperature, and the power generated by this incinerator is quite difficult for ordinary users. Because the resulting data is stored in a data logger that can only be downloaded in the form of excel files and cannot be known directly (real-time). This makes it difficult to know when the temperature of the device has decreased, and the amount of power generated by the device. At UD Nadi Utama itself, its human resources have a good ability to use the web system on their mobile devices. From the problems with the conversion tool and the potential of human resources at UD Nadi Utama. A website-based monitoring system is created, which displays the data generated by the data logger in almost real time.